СONVERGENCE OF MD-CHAIN AND VELOCITY AUTOCORRELATION FUNCTIONS OF ELECTRONS FOR A DENSE SEMICLASSICAL PLASMA - Nigmetova, G.N. (Recent Contributions to Physics, 2018)
The microscopic (dynamical) properties of a dense semiclassical plasma were investigated by molecular dynamics method. The semiclassical model of nonideal plasma was used. The potential part of MD-chain and velocity autocorrelation functions of electrons for semiclassical plasma.